KORELASI DHOMMAH SEBAGAI TANDA ROFA’; Studi Sikap Kepemimpinan Ideal Dalam Perspektif Islam - Nabila Arrahma; Nissa Zahra Silmy Damanik (Jurnal Shaf, 2025)
This article aims to explores the symbolic meaning of dhammah as a grammatical marker of rafa’ in Arabic and its relevance to ideal leadership in Islam. Using a qualitative library research method, the study draws on nahwu texts, academic articles, and Islamic sources such as the Qur’an and Hadiths. The analysis highlights how dhammah, which elevates a word’s position in a sentence, represents that leadership should be granted based on merit and noble character, not force. Like dhammah maintains grammatical balance, a leader is expected to uphold social harmony through justice and responsibility. Misplacing dhammah can drastically change a sentence’s meaning, just as leadership mistakes can deeply impact society. Thus, dhammah is not only a grammatical tool but also a metaphor for ethical leadership—emphasizing worthiness, moral integrity, and balanced governance. This study reveals the philosophical depth of Arabic grammar in illustrating Islamic leadership principles through linguistic symbolism.